Effect Of Organizational Culture And Job Stress On Employee Performance at PT.PLN (Persero) Majalaya Area - Rizki Piscal Aliansyah; Mariana Rachmawati (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
This study aims to determine how much influence organizational culture and job stress have on employee performance at PT. PLN (PERSERO) Majalaya Area. The research method used is descriptive and verification. Data collection techniques through interviews, observations and questionnaires. The sample in this study were 62 employees. The results of this study indicate that there is a significant influence between organizational culture on the performance of employees of PT. PLN (Persero) Majalaya Area based on the partial calculation of the coefficient of determination, which is 68.06%. There is a significant influence between job stress on the performance of employees of PT. PLN (Persero) Majalaya Area based on the partial calculation of the coefficient of determination, which is 56.55%. There is a significant influence between organizational culture and job stress on the performance of employees of PT. PLN (Persero) Majalaya Area based on the calculation of the coefficient of determination simultaneously, which is 73.6% and the remaining variables are not examined in this study